A relação entre sexo e idade e queixas de crianças em psicoterapia - Konrat, Carolina Elisa Diesel (2012)
The present dissertation is composed of two studies, following the rules of the program of Post-Graduation in Psychology at PUCRS. The first of them is a review of literature entitled Studies about complaints in outpatient clinics , which had as an aim to verify how is the profile of children in attendance characterized over time in terms of the variables sex, age and complaints that lead to the search of treatment. For this study, bibliographical search was done to the basis data of Scielo, Lilacs, PsycInfo e IndexPsi. The results showed that few works treat these variables in an inferential way, which doesn t allow us to emit any opinion about the patients profile. Therefore, this issue continues to deserve attention, as the accurate knowledge of the patients makes it possible to take decisions about the best strategies of attendance. The second study is of empirical character and is entitled Complaints and sex and age in children in clinical-schools centers . It had as an aim to verify the relationship between sex, age and complaints that lead children to the clinical-school centers in search of psychological care in the form of evaluation and/or attendance. Thirty protocols, conceded under the caution of ethical principles, from three institutions were analyzed. The sample was composed of 1550 boys (64,3%) and 861 girls (35,7%), within the ages of five to 12 years old. The relationship between the three variables of interest - has shown itself significant, from the statistical point of view, in the sense that girls in relation to boys, present more behaviors related to the Anxiety/Depression and Retraction/Depression within the age group of 5 to 6 years; only related to the behavior of Anxiety/Depression, the girls continue to have higher scores than the boys in the age groups of 7 to 8 and 9 to 10 years old; in the age groups of 5 to 6, 7 to 8, 9 to 10 and 11 to 12 years old, the boys always present more attention problems than the girls; there is more aggressive behavior in boys only in the age group of 5 to 6 years old; however, the challenging behavior appears more in girls than in boys in the age group of 9 to 10 years old.